Distribution of Intravenously Administered Acetylcholinesterase Inhibitor and Acetylcholinesterase Activity in the Adrenal Gland: 11C-Donepezil PET Study in the Normal Rat - Watabe, Tadashi; Naka, Sadahiro; Ikeda, Hayato; Horitsugi, Genki; Kanai, Yasukazu; Isohashi, Kayako; Ishibashi, Mana; Kato, Hiroki; Shimosegawa, Eku; Watabe, Hiroshi; Hatazawa, Jun (PLOS ONE, 2014)
Purpose Acetylcholinesterase (AChE) inhibitors have been used for patients with Alzheimer's disease. However, its pharmacokinetics in non-target organs other than the brain has not been clarified yet. The purpose of this study was to evaluate the relationship between the whole-body distribution of intravenously administered 11C-Donepezil (DNP) and the AChE activity in the normal rat, with special focus on the adrenal glands. Methods The distribution of 11C-DNP was investigated by PET/CT in 6 normal male Wistar rats (8 weeks old, body weight = 220±8.9 g). A 30-min dynamic scan was started simultaneously with an intravenous bolus injection of 11C-DNP (45.0±10.7 MBq). The whole-body distribution of the 11C-DNP PET was evaluated based on the Vt (total distribution volume) by Logan-plot analysis. A fluorometric assay was performed to quantify the AChE activity in homogenized tissue solutions of the major organs. Results The PET analysis using Vt showed that the adrenal glands had the 2nd highest level of 11C-DNP in the body (following the liver) (13.33±1.08 and 19.43±1.29 ml/cm3, respectively), indicating that the distribution of 11C-DNP was the highest in the adrenal glands, except for that in the excretory organs. The AChE activity was the third highest in the adrenal glands (following the small intestine and the stomach) (24.9±1.6, 83.1±3.0, and 38.5±8.1 mU/mg, respectively), indicating high activity of AChE in the adrenal glands. Conclusions We demonstrated the whole-body distribution of 11C-DNP by PET and the AChE activity in the major organs by fluorometric assay in the normal rat. High accumulation of 11C-DNP was observed in the adrenal glands, which suggested the risk of enhanced cholinergic synaptic transmission by the use of AChE inhibitors.